THE ESSENCE OF LEADER MANAGERIAL COMPETENCIES IN EDUCATIONAL TRANSFORMATION: ANALYSIS OF THE 2024 EDUCATION REPORT - Sari, Puspita; Rosnelli, Rosnelli; Mudjisusatyo, Yuniarto; Rahman, Arif (Universitas Muhammadiyah Mataram, 2025)
Data is an important element in policy making, especially in educational management in the transformation era. In addition to data, managerial competencies of educational leaders who are adaptive to change are also needed. Both will strengthen the running of educational organizations. This study aims to analyze the nature of managerial competencies of leaders in educational transformation while analyzing education report as a basis for educational policy making. This study uses a descriptive method with a constructivist approach that relies on secondary data, namely regional education report and literature on leadership and managerial competencies. The analysis process is carried out by identifying educational problems, then mapping them with an Ishikawa diagram. Alternative solutions to problems related to programs and policies that touch on the technical realm are not discussed in depth, because the analysis focuses more on the concept of managerial competencies of educational leaders. The results of the study are in the form of a concept of managerial competencies of leaders in educational transformation that includes 3 domains of knowledge, skills, and managerial attitudes, consisting of (1) data literacy and databased decision making, (2) reflective and contextual leadership, (3) human resource development and organizational culture, (4) technology and innovation management, (5) interpersonal skills and organizational ethics, (6) focus on the functions, duties and attitudes of managers. This research provides practical implications, namely as a role model for increasing the capacity of regional education leaders, and theoretical implications, namely as a basis for further research in the field.